Portable normothermic ex-vivo lung perfusion, ventilation, and functional assessment with the Organ Care System on donor lung use for transplantation from extended-criteria donors (EXPAND): a single-arm, pivotal trial. Issue 11 (November 2019) - Loor, Gabriel; Warnecke, Gregor; Villavicencio, Mauricio A; Smith, Michael A; Kukreja, Jasleen; Ardehali, Abbas; Hartwig, Matthew; Daneshmand, Mani A; Hertz, Marshall I; Huddleston, Stephen; Haverich, Axel; Madsen, Joren C; et al.
Summary: Background: Donor lung use for transplantation is the lowest among solid organ tranplants because of several complex and multifactorial reasons; one area that could have a substantial role is the limited capabilities of cold ischaemic storage. The aim of the EXPAND trial was to evaluate the efficacy of normothermic portable Organ Care System (OCS) Lung perfusion and ventilation on donor lung use from extended-criteria donors and donors after circulatory death, which are rarely used. Methods: In this single-arm, pivotal trial done in eight institutions across the USA, Germany, and Belgium, lungs from extended-criteria donors were included if fulfilling one or more of the following criteria: a ratio of partial pressure of arterial oxygen (PaO2 ) to fractional concentration of oxygen inspired air (FiO2 ) in the donor lung of 300 mm Hg or less; expected ischaemic time longer than 6 h; donor age 55 years or older; or lungs from donors after circulatory death that were recruited and assessed using OCS Lung. Lungs were transplanted if they showed stability of OCS Lung variables, PaO2 :FiO2 was more than 300 mm Hg, and they were accepted by the transplanting surgeon. Patients were adult bilateral lung transplant recipients. The primary efficacy endpoint was a composite of patient survival at day 30 post-transplant and absence of The International Society for Heart & Lung Tranplantation primary-graft dysfunction grade 3 (PGD3) within 72 h post-transplantation, with a prespecified objective performance goal of 65%. The primary analysis population was all transplanted recipients. This trial is registered with ClinicalTrials.gov, number NCT01963780, and is now complete. Findings: Between Jan 23, 2014, and Oct 23, 2016, 93 lung pairs were perfused, ventilated, and assessed on the OCS Lung. 12 lungs did not meet OCS transplantation criteria so 81 lungs were suitable for transplantation. Two lungs were excluded for logistical reasons, hence 79 (87%) of eligible lungs were transplanted. The primary endpoint was achieved in 43 (54%) of 79 patients and did not meet the objective performance goal. 35 (44%) of 79 patients had PGD3 within the initial 72 h. 78 (99%) of 79 patients had survived at 30 days post-transplant. The mean number of lung graft-related serious adverse events (respiratory failure and major pulmonary-related infection) was 0·3 events per patient (SD 0·5). Interpretation: Despite missing the objective primary endpoint, the portable OCS Lung resulted in 87% donor lung use for transplantation with excellent clinical outcomes. Many lungs declined by other transplant centres were successfully transplanted using this new technology, which implies its use has the potential to increase the number of lung transplants performed worldwide. Whether similar outcomes could be obtained if these lungs were preserved on ice is unknown and remains an area for future research. Funding: TransMedics Inc.